Oral antithrombotic therapy for the prevention of recurrent cerebrovascular events. Issue 4 (10th August 2021) - Capodanno, Davide; Angiolillo, Dominick J
Abstract: Stroke is frequently a disabling and even life-threatening condition that has an ischaemic cause in most cases. Transient ischaemic attack (TIA) is a lower risk condition that still exposes to the risk of future major cardiovascular events. The causes of stroke can be classified as cardioembolic disease, large vessel disease, small vessel disease, undetermined, or others. Cardioembolic disease and atherothrombosis of large arteries are the most common underlying processes of ischaemic stroke and TIA. Therefore, antithrombotic therapy is a central strategy in the pharmacological management of these patients. However, because antithrombotic therapy provides ischaemic protection at the price of increased bleeding, defining the fine balance between efficacy and safety is a clinical challenge. Numerous trials have recently defined the current indications to the use of anticoagulant and antiplatelet therapy in patients with various subtypes of ischaemic stroke or TIA. In this review, we provide an updated appraisal of the currently available evidence on the use of various oral antithrombotic agents for prevention of recurrent events after an ischaemic stroke or TIA. Graphical Abstract: